IDENTIFIKASI POTENSI JENIS TANAMAN AGROFORESTRY POLA DUSUNG DI NEGERI WAKAL, KECAMATAN LEIHITU, KABUPATEN MALUKU TENGAH, PROVINSI MALUKU - Upuolat, Firhan; Wattimena, Cornelia; Talaohu, Moda (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to explore the potential of agroforestry plants in Dusung, Negeri Wakal. The research methods included field observation, vegetation inventory, and interviews with local farmers, analyzed using the Importance Value Index (IVI) and the Shannon-Wiener Diversity Index. The results revealed that high-economic-value plants such as clove (Syzygium aromaticum), nutmeg (Myristica fragrans), durian (Durio zibethinus), and coffee (Coffea arabica) are prioritized by the community due to their significant market value. Vegetation structure analysis identified that clove raja (Syzygium obtusifolium) dominates the sapling and pole stages, while water apple (Syzygium aqueum) and Indonesian bay leaf (Syzygium polyanthum) are predominant at the tree level. The biodiversity index is categorized as moderate, reflecting a balance between species diversity and the dominance of economically valuable plants. The distribution of plant species is influenced by ecological adaptation, market demand, and community management practices. In conclusion, agroforestry management in Dusung Wakal effectively prioritizes high-economic-value plants that are well-adapted to the environment. However, efforts to preserve biodiversity remain essential to ensure ecosystem sustainability and long-term benefits.